The Influence of Decision Task on the Magnitude of Decoy and Compromise Effects in a Travel Decision. (September 2019) - Kim, Jungkeun; Kim, Peter Beomcheol; Lee, Jin-Soo; Kim, Seongseop (Sam); Hyde, Kenneth F.
This research assesses the effects of choice alternatives on the travel destination decisions of travelers. The decoy effect involves the addition of a new inferior alternative into a choice set, thereby increasing the choice of an existing option. Meanwhile, the compromise effect involves the addition of a new alternative into a choice set that increases selection of an existing option with nonextreme attributes, and decreases selection of options with extreme attributes. In this study, a series of scenario-based experiments is performed to determine if the decoy and compromise effects influence travel destination decisions. Results show that the decoy effect is stronger in a choice (vs. rejection) task, whereas the compromise effect is stronger in a rejection (vs. choice) task when deciding travel destinations.